Large-Area Synthesis of Layered HfS2(1- x )Se2 x Alloys with Fully Tunable Chemical Compositions and Bandgaps - Wang, Denggui (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim.